4(z+4)=9(z-6)

Simple and best practice solution for 4(z+4)=9(z-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(z+4)=9(z-6) equation:


Simplifying
4(z + 4) = 9(z + -6)

Reorder the terms:
4(4 + z) = 9(z + -6)
(4 * 4 + z * 4) = 9(z + -6)
(16 + 4z) = 9(z + -6)

Reorder the terms:
16 + 4z = 9(-6 + z)
16 + 4z = (-6 * 9 + z * 9)
16 + 4z = (-54 + 9z)

Solving
16 + 4z = -54 + 9z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-9z' to each side of the equation.
16 + 4z + -9z = -54 + 9z + -9z

Combine like terms: 4z + -9z = -5z
16 + -5z = -54 + 9z + -9z

Combine like terms: 9z + -9z = 0
16 + -5z = -54 + 0
16 + -5z = -54

Add '-16' to each side of the equation.
16 + -16 + -5z = -54 + -16

Combine like terms: 16 + -16 = 0
0 + -5z = -54 + -16
-5z = -54 + -16

Combine like terms: -54 + -16 = -70
-5z = -70

Divide each side by '-5'.
z = 14

Simplifying
z = 14

See similar equations:

| 32.1522=16/T | | 6x^2+24x=-24 | | 272=-16t^2+129+42 | | (x+7)(x-10)=0 | | 9/2=v/5 | | 1/4x-8=2x-29 | | 1.73205080757x+2=2.64575131106+2 | | (3w)+(7w+w^2)=A | | 113-v=241 | | c(x)=20x+700 | | 5x+6x+7x-3= | | 8y+6=20 | | -101=-8(p+3)-3p | | 2x=x^2-10 | | 2(x+1)-3=5 | | 900=10x+(100-10x) | | 12x^2+5x-19=0 | | 3/2*5=a | | 21x-7x=3-4x | | 2xsquared+15=-13x | | 2x(2x-5)=0 | | 4-5h+8=-2 | | 9x+2x-x=2(100+3x) | | 128=16t^2+96t | | 2(7+28)= | | 16x+44y=20 | | (18-3i)(-7+8i)=0 | | 24=4x-1 | | 2(7+w)+2(w)=126 | | -5x-2.8=9x+0.4 | | -9i(4+12i)=0 | | 2(7+w)+2(w)= |

Equations solver categories